The Roman mortuary landscape and its family relationships from the perspective of Seneca (AD 62) - Munhoz de Omena, Luciane; Procópio de Carvalho, Dyeenmes (Romanitas - Revista de Estudos Grecolatinos, 2023)
The Roman society shared burial practices aimed at respecting the deceased and perpetuating their names in the sacred landscape of necropolises. Built along the city's access roads, today we can still explore numerous archaeological sites that gift visitors with monumental burial structures, which are related to various social interests and practices. This article aims to understand representations of death and its relations with the memory from mortuary landscape and its family relationships in the philosophical logos of Lucius Annaeus Seneca by examining the impact representations of death in the Neron court at the time of AD 62. From there, we will make some critical reflections on the aristocratic behaviours regarding to the family and the mourning, thus, by analysing the practice of uirtus, we wil understand the creation of behavioural rules to the public expression of pain and the insertion of more particular and emotional dimensions in the way they reminded of the dead from the perspective of Seneca.
Keywords: Mortuary landscape; Family; Seneca; Rome